Provision of mother's own milk for preterm infants during the COVID-19 pandemic: Differential effect of insurance - Lauren E. Boudreau; Lauren E. Boudreau; Betty R. Vohr; Betty R. Vohr; Richard Tucker; Elisabeth C. McGowan; Elisabeth C. McGowan (Frontiers Media S.A., 2022)
Mother-infant dyads faced many challenges during the COVID-19 pandemic; however, the impact was different depending on socio-economic determinants. This study aims to investigate the impact of the COVID-19 pandemic on maternal provision of mother's own milk (MOM) at neonatal intensive care unit (NICU) discharge among preterm infants. We hypothesized that fewer infants would be discharged home on any MOM during the pandemic period compared to a pre-pandemic period. This is a retrospective analysis of infants born <34 weeks' gestation admitted to the Women and Infant's Hospital NICU. Infants born pre-pandemic (1/1/2019 to 2/29/2020) were compared to infants born during the pandemic (3/1/2020 to 4/30/2021). Maternal and neonatal variables were analyzed by group. The primary outcome was provision of MOM (defined as feeding exclusively MOM, or a combination of MOM and formula) at NICU discharge. Analyses were performed for time periods, and multivariable regression analyses were run for the total cohort and by insurance type. Analysis included 268 infants born pre-pandemic and 262 infants born during the pandemic. Pandemic group mothers vs. pre-pandemic were less likely to be single (27%, 63/233 vs. 38%, 93/243; p = 0.01) and more likely to have a diagnosis of chorioamnionitis (16%, 38/236 vs. 7%, 17/243; p = 0.002). Rates of public insurance were similar (55% pre-pandemic and 50% pandemic). There was no significant change in provision of MOM between time periods. In multivariable analysis, public insurance decreased the odds of MOM at discharge for the entire study period (aOR 0.31, 95% CI: 0.19-0.50; p = 0.0001). On analysis by insurance type, rates of MOM increased from 77% pre-pandemic to 88% during the pandemic (p = 0.03) for mothers with private insurance and remained unchanged for mothers with public insurance (52% pre-pandemic and 53% pandemic; p = 0.86). Mothers with private insurance had twice the odds (aOR 2.02, 95% CI: 1.02-3.97; p = 0.04) of providing MOM during the pandemic vs. pre-pandemic. For those with public insurance, the odds for any MOM provision during the pandemic were unchanged (aOR 0.95, 95% CI: 0.5-1.7; p = 0.86). These differences may be related to health care disparities requiring additional exploration of risk factors and the need for equitable opportunities for all mother-infant dyads.